2013
DOI: 10.1242/dev.092320
|View full text |Cite
|
Sign up to set email alerts
|

Src kinases mediate the interaction of the apical determinant Bazooka/PAR3 with STAT92E and increase signalling efficiency in Drosophila ectodermal cells

Abstract: SUMMARYIntercellular communication depends on the correct organization of the signal transduction complexes. In many signalling pathways, the mechanisms controlling the overall cell polarity also localize components of these pathways to different domains of the plasma membrane. In the Drosophila ectoderm, the JAK/STAT pathway components are highly polarized with apical localization of the receptor, the associated kinase and the STAT92E protein itself. The apical localization of STAT92E is independent of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…Since Src42a is known to signal downstream of Draper and has been shown to mediate Stat92E signaling in multiple contexts [25],[55],[56], we sought to determine whether Src42a activity was sufficient to activate Stat92E transcriptional reporters. Indeed, expression of a constitutively active Src42a molecule (Src42a CA ) resulted in robust 10XStat92E-dGFP reporter activation throughout brain (Figure 5C, refer to Figure 4B for control).…”
Section: Resultsmentioning
confidence: 99%
“…Since Src42a is known to signal downstream of Draper and has been shown to mediate Stat92E signaling in multiple contexts [25],[55],[56], we sought to determine whether Src42a activity was sufficient to activate Stat92E transcriptional reporters. Indeed, expression of a constitutively active Src42a molecule (Src42a CA ) resulted in robust 10XStat92E-dGFP reporter activation throughout brain (Figure 5C, refer to Figure 4B for control).…”
Section: Resultsmentioning
confidence: 99%
“…This data suggests that Src64B expression exerts an additional effect on ab -expressing cells to inhibit Dll gene expression and differentiation. Src upregulation activates the JNK and Stat signalling pathways, affects adherens junction function and represses Hippo signalling ( Enomoto and Igaki, 2013 ; Kohlmaier et al, 2014 ; Ma et al, 2013 ; Read et al, 2004 ; Sotillos et al, 2013 ; Vidal et al, 2006 ). Furthermore, recent studies have shown that overexpression of Src64B in the Drosophila intestinal stem cells can alter differentiation and result in amplification of progenitor cell pools ( Cordero et al, 2014 ; Kohlmaier et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently a small molecule inhibitor targeting Bcl6 has been developed, and combining this with a Stat3 inhibitor resulted in enhanced cell killing in triple negative breast cancer cell lines ( Walker et al, 2014 ). Since in Drosophila and human cells, Src upregulates Stat activity ( Cordero et al, 2014 ; Frame, 2004 ; Kohlmaier et al, 2014 ; Read et al, 2004 ; Sotillos et al, 2013 ), tumours showing high Bcl6 and Src or Yes1 expression would be predicted to be sensitive to this combined therapeutic regime. Interestingly, a predominance of the significant correlations that were observed in the human epithelial cancer datasets with either Bcl6 or ZBTB7A involved upregulation of JNKK and JNK family genes.…”
Section: Discussionmentioning
confidence: 99%
“…Border cell motility has been likened to an EMT event; however, border cells move as a collective that retain some epithelial character. In particular, apical–basal polarity components are required [183,184,185]. Additionally, while downregulation of E-cadherin is known as a classic marker of EMT, in border cells it must be maintained.…”
Section: Jak/stat Signaling Promotes Cell Motility and Metastasismentioning
confidence: 99%